Association between Vitamin D Status and Mortality among Adults with Diabetic Kidney Disease - Feng Xu; Hongyu Lu; Tianwen Lai; Ling Lin; Yongsong Chen (Journal of Diabetes Research)
Objective. Emerging evidence demonstrates that vitamin D status contributes to the incidence of diabetic kidney disease (DKD). However, the causal relationships between vitamin D and mortality among individuals with DKD are inconclusive. Our study is aimed at exploring the relationship between serum 25-hydroxyvitamin D (25(OH)D) concentrations and mortality among adults with DKD. Research Design and Methods. Our study included 1,202 adult participants with DKD from the National Health and Nutrition Examination Survey (NHANES) 2001–2014. Cox and competing-risks regression were used to estimate hazard ratios (HRs) and 95% CIs for associations between 25(OH)D concentrations and survival. Results. The overall mean serum 25(OH)D concentration was 55.9±26.3. Vitamin D deficiency (25OHD<50 nmol/l), insufficiency group (50≤25OHD<75 nmol/l), and sufficiency group (25OHD≥75 nmol/l) were observed in 552 (45.9%), 409 (34.0%), and 241 (20.0%) participants, respectively. Higher levels of vitamin D were significantly associated with improved all-cause and nonaccident- and malignant neoplasm-cause mortality among individuals with DKD after adjusting for the potential confounding factors. Conclusions. We observed widespread vitamin D deficiency or insufficiency in DKD patients. Higher 25(OH)D values were significantly correlated with lower risk of mortality after adjusting for confounding variables.